2015
DOI: 10.1055/s-0035-1555781
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition, Muscle Quality and Scoliosis in Female Collegiate Gymnasts: A Pilot Study

Abstract: Research has demonstrated an elevated prevalence of body weight concerns and scoliosis among female gymnasts. The purpose of the current study was to evaluate relationships between body composition, muscle quality, and performance in female collegiate gymnasts (n=15), and to evaluate the prevalence of scoliosis. Dual-energy X-ray absorptiometry was used to evaluate body composition and lateral spinal curvature using a modified version of the Ferguson method. Echo intensity (EI) and cross-sectional area (CSA) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 24 publications
1
21
2
3
Order By: Relevance
“…In comparison to the aerialists, the gymnasts had a lower BF%, although age differences between the gymnasts (16.9 ± 3.6 years) and the aerialists (32.8 ± 6.3 years) should be taken into consideration [ 21 ]. In contrast, an investigation on female collegiate gymnasts found the athletes to have BF% of 23.2 ± 3.2, which are higher than the BF% of aerialists determined in the present investigation [ 22 ]. Differences in BF% between athletes are likely due to the nature of their physical activity [ 21 ].…”
Section: Discussioncontrasting
confidence: 98%
“…In comparison to the aerialists, the gymnasts had a lower BF%, although age differences between the gymnasts (16.9 ± 3.6 years) and the aerialists (32.8 ± 6.3 years) should be taken into consideration [ 21 ]. In contrast, an investigation on female collegiate gymnasts found the athletes to have BF% of 23.2 ± 3.2, which are higher than the BF% of aerialists determined in the present investigation [ 22 ]. Differences in BF% between athletes are likely due to the nature of their physical activity [ 21 ].…”
Section: Discussioncontrasting
confidence: 98%
“…Valid and reliable body composition techniques are essential for detecting clinical conditions associated with both over- and under-fatness, overall health, injury prevention, and tracking changes from diet and exercise [2, 4, 30, 32-34]. Despite the known improvement in precision when using a multi-compartment model for body composition, many researchers, clinicians, and coaches still use single 2C techniques or DEXA (3C) as methods for determining body composition.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional research has demonstrated that body composition differs among position groups (5, 7, 29, 32), and has identified a clear trend of increasing body size in recent decades (2, 16, 33, 35). American football requires a unique combination of speed, size, and power (12); as such, indices of body size and composition have been associated with strength (36), power (30), and career earnings (33) in football players, and extensive research in a variety of populations has documented relationships between various indices of fat-free mass (FFM) and strength, power, speed, and sport performance (1, 3, 24, 27, 28, 41, 43). However, absolute amounts of FFM are influenced by height, with greater height favoring higher FFM.…”
Section: Introductionmentioning
confidence: 99%